Fungsional Struktural Parson dalam Perubahan Sosial Desa Ponggok: Telaah Linimasa 2009 – 2023 - Iqmal Maulana Z; Zahran Fauzi H; Yilmaz Omar S; Ahsan Syamil R; Dede Sri Kartini (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study analyzes social change in Ponggok Village, Klaten, Central Java, from an impoverished village to a self-sufficient one, utilizing Talcott Parsons' structural functionalist framework and the AGIL model (Adaptation, Goal Attainment, Integration, Latency). Prior to 2006, Ponggok Village faced poverty, inadequate infrastructure, and limited employment opportunities, despite its significant potential for spring water. The transformation began in 2009-2013 with collaboration between the village head and academics for potential mapping and the establishment of the Village-Owned Enterprise (BUMDes) Tirta Mandiri. The period from 2014 to 2018 marked a "golden era" with the implementation of the Village Law of 2014, increased village funds, and peak revenues from Umbul Ponggok. However, from 2019-2023, the village experienced a significant decline due to the COVID-19 pandemic. A descriptive qualitative research method with a case study approach was employed, dividing the timeline into three periods (2009-2013, 2014-2018, 2019-2023). Data were collected through Focus Group Discussions, interviews, and literature reviews. The research findings demonstrate how Ponggok Village systematically fulfills the AGIL functional prerequisites by examining socio-economic policies through policies implemented by the Village Government, Village Consultative Body (BPD), and Village-Owned Enterprise (BUMDes) in efforts to improve quality of life, foster social integration among stakeholders, and maintain values through sustainable programs aimed at achieving and sustaining the success of its transformation. These findings provide a holistic understanding of the village’s resilience and adaptability in facing social and economic challenges.